Designing a Low-Budget Secure Network for SMEs: Threat Landscape, Virtualization and Data Storage - Mateusz KRAUZE; Mariusz ZAL (Communications of International Proceedings, 2025)
Small and medium-sized enterprises (SMEs) remain highly exposed to advanced cyber threats despite their growing dependence on digital services. This study is motivated by the persistent resource gap between SMEs and large organisations, which prevents smaller entities from adopting resilient, security-by-design infrastructures. Although numerous guidelines and frameworks for SME cybersecurity exist, the literature lacks a unified, practical, and empirically grounded architectural blueprint that integrates low-cost virtualization, modern storage systems, and selective cloud services into a coherent, security-enhancing environment. To address this gap, the study conducts a comparative analysis of key infrastructure technologies relevant to SME cybersecurity. The methodology combines feature-based evaluation of widely used virtualization platforms (KVM, Proxmox VE, Hyper-V, VMware vSphere), assessment of data storage solutions (NAS, SAN, and Software-Defined Storage), and examination of selected IaaS/PaaS cloud services suitable for low-budget deployments. The analysis emphasises cost structure, security capabilities, manageability, and failure-resilience characteristics. The findings demonstrate that SMEs can significantly strengthen their cyber resilience by adopting an open-source-centric, hybrid architecture that leverages commodity hardware for on-premise virtualization and storage while offloading selected functions to cloud services. The proposed reference architecture provides improved redundancy, streamlined management, and enhanced protection against common threats such as ransomware, credential compromise, and service downtime. The study contributes a practical, implementable model that allows SMEs to transition from fragmented and vulnerable infrastructures toward robust, corporate-class environments that meaningfully support business continuity and cybersecurity.
Keywords: SME; cybersecurity; IT infrastructure; virtualization; data storage; cloud computing; low-budget corporate-class architecture